Spirit matters: occult beliefs, alternative religions, and the crisis of faith in Victorian Britain - Franklin, J. Jeffrey (Cornell University Press, 2018)
Orthodox Christianity, scientific materialism, and alternative religions -- The evolution of occult spirituality in Victorian England and the representative case of Edward Bulwer-Lytton -- Anthony Trollope's religion : the orthodox/heterodox boundary -- The influences of Buddhism and comparative religion on Matthew Arnold's theology -- Interpenetration of religion and national politics in Great Britain and Sri Lanka : William Knighton's Forest life in Ceylon -- Identity, genre, and religion in Anna Leonowens' The English governess at the Siamese court -- Ancient Egyptian religion in late-Victorian England -- The economics of immortality : the demi-immortal Oriental, Enlightenment vitalism, and political economy in Bram Stoker's Dracula -- Conclusion : from Victorian occultism to new age spiritualities